Experimental Study on the Flexural Behavior of Reinforced Polystyrene Blocks in Concrete Beams - Lim Yong Tat; Ling Jen Hua; Lau Ji Wei; Alicia Yik Yee Min (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
A new type of lightweight beam system was recently proposed by embedding polystyrene in beams to improve structural efficiency. This removes the non-performing concrete in the neutral axis and tension region to provide a comparable strength as a solid beam. There are, however, limited studies conducted to investigate the structural behavior of such beams. Therefore, this research presents an experimental investigation to assess the effect of polystyrene shapes in the beams. This involved testing a solid beam and five lightweight beams under flexural load using a four-point load test. The inclusion of polystyrene was estimated to have reduced the self-weight of beams by 8.6% to 11.8% when compared with the solid beam. The results also showed the ellipse polystyrene with a width of 70 mm and height of 50 mm produced the highest effective strength to weight ratio (sw) of 1.12 and performed 12% better than the solid beam. Moreover, the lightweight beams have more weight reduced than the strength, and those with ellipse polystyrene were found to have performed better than circular ones based on first crack load, ultimate load, and effective strength to weight ratio (sw). The beams with ellipse polystyrene allowed better stress distribution and this gave them a higher strength than sphere shape. For industry application, the polystyrene content is recommended to be greater than 10% while the effective strength to weight ratio (sw) of the beam is greater than 1. The successful reduction of the weight without affecting the structural performance has the ability to help in reducing construction costs.